The Role Of Sharia Financial Education And Literacy In Increasing Community Economic Participation - Sari, Yesa Tiara Purnama; Rufaida, Alfi Maulisa; Hasanah, Uswatun (Doktoral Ilmu Manajemen, Universitas Pasundan, 2024)
This article discusses the role of sharia financial education and literacy in increasing community economic participation. In an era where Islamic finance is increasingly in demand, a good understanding of Islamic financial principles and products is crucial. This research uses qualitative methods with literature analysis and in-depth interviews to explore the extent to which Islamic financial literacy influences economic participation. The research results show that increasing sharia financial literacy contributes significantly to increasing economic participation through better understanding of sharia financial products, increased trust in the sharia financial system, and wiser financial decision making. This article recommends that financial institutions, governments and educational institutions improve sharia financial education and literacy programs to encourage financial inclusion and economic prosperity in society.